Velocity models of the upper mantle of the continental and oceanic rifts - V. V. Gordienko; L. Ya. Gordienko (Геофизический журнал, 2017)
The 1-D velocity models of longitudinal seismic waves distribution for the upper mantle of the continent rift systems which directly border with the mid-oceanic ridges (MOR) are constructed. A difference in the models between the named types of structures is established. Near the continents (but located on the oceanic crust) MOR velocity sections do not practically differ from those established on the oceans. The maximum speed anomalies are presented here. Under continental rift systems, the anomaly is less, in some cases because of the presence of arrays not covered by rifting processes within them, or the processes take place at untypical conditions. Velocity models corresponding to schemes of deep-seated processes on the advection-polymorphic hypothesis are constructed. Their comparison with experimental data (in part, according to the literature data) has been carried out. Their consistency is established.